2012
DOI: 10.1159/000338937
|View full text |Cite
|
Sign up to set email alerts
|

Specific Immunotherapy Normalizes Tryptophan Concentrations in Patients with Allergic Rhinitis

Abstract: <b><i>Background/Aims:</i></b> An immune shift towards Th2-type immunity seems to be critical in the pathogenesis of allergic asthma and rhinitis. In a previous study, we found higher serum tryptophan concentrations in patients with seasonal tree or grass pollen rhinoconjunctivitis who underwent specific immunotherapy (SCIT) than in controls, and those with the highest levels at baseline responded less well to SCIT. In the present study, we examined whether ‘booster immunotherapy’ after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Interestingly, higher levels of tryptophan were preferentially observed in nonresponders to SCIT. Thus, it was concluded that tryptophan concentrations could help to predict the outcome of SCIT [63].…”
Section: Tryptophan In Allergymentioning
confidence: 99%
“…Interestingly, higher levels of tryptophan were preferentially observed in nonresponders to SCIT. Thus, it was concluded that tryptophan concentrations could help to predict the outcome of SCIT [63].…”
Section: Tryptophan In Allergymentioning
confidence: 99%
“…Booster immunotherapy in hay fever patients induced a decrease in serum tryptophan and kynurenine concentrations, demonstrating the involvement of tryptophan metabolism in the course of allergic responses. 100 …”
Section: Asthma and Copd: Defective Activation Of The Kynurenine Path...mentioning
confidence: 99%